The Founders - Nathan Bartel (Symphony in the Flint Hills, 2017)
Introduction: The Chisholm Trail was no one’s idea. No single individual cut a path from Texas to Kansas. No one person emerged from the instability and confusion of the postbellum Great Plains to say, “This is how the cattle industry can thrive today.” No one could claim he discovered the trail; no one could claim it as his.
Keywords: Chisholm Trail; Great Plains